Analisis Kebijakan Kurikulum Merdeka Dalam Mewujudkan Pemerataan Mutu Pendidikan Di Indonesia - Nur Atik Azkiyah; Abd Rozak (Indonesian Journal of Islamic Educational Management, 2025)
Education is the main foundation for the progress of a nation, but in Indonesia, disparities in the quality of education are still a serious challenge, especially between urban and rural areas, as well as developed and remote areas. This gap is caused by limited infrastructure, uneven distribution of teachers, varying quality of teacher training, and the relevance of the curriculum to local needs. To overcome this problem, the Ministry of Education, Culture, Research, and Technology launched the Independent Curriculum Policy, with the aim of creating more flexible, relevant, and student-centered learning, as well as providing greater autonomy to educational units. This article aims to analyze how the Independent Curriculum policy can play a role in realizing equitable quality of education in Indonesia, as well as identify implementation challenges and provide strategic recommendations. This study uses a qualitative method with literature review. The results of the study show that the implementation of the Independent Curriculum faces various challenges in realizing equitable quality of education. Key challenges include inequalities in readiness between regions, where schools in 3T (disadvantaged, frontier, outermost) areas struggle to access resources, teacher training, and technology facilities. The varying quality and readiness of teachers, as well as the administrative burden, also hinder optimal roles. The flexibility of the curriculum, which should be an advantage, actually causes confusion for teachers due to the lack of detailed technical guidelines. In addition, general policy evaluation without considering the local context and weak involvement of local governments further exacerbates the problem of equity. Therefore, cross-sectoral commitment, equitable distribution of resources, and comprehensive reform of the education system are needed to achieve equitable distribution of the quality of education